Cold spray deposition of Cr2AlC MAX phase for coatings and bond-coat layers. Issue 4 (April 2019) - Go, T.; Sohn, Y.J.; Mauer, G.; Vaßen, R.; Gonzalez-Julian, J.
Abstract: Highly pure Cr2 AlC powders were synthesized and deposited for the first time by cold spray technology on stainless steel substrates. The Cr2 AlC coatings were relative dense, up to 91%, and present high purity (> 98%) since only small traces of Cr2 Al, Al2 O3 and Cr2 O3 were detected by XRD, SEM and EDX. The microstructure of the coatings is homogeneous, although some preferential orientation in the basal plane was observed by XRD pole figures. The adhesion between the coating and the substrate is strong, and compressive residual stresses up to 300 MPa in the coating were determined by XRD. Furthermore, a conventional YSZ Thermal Barrier Coating (TBCs) was deposited by Atmospheric Plasma Spray (APS) on top of the cold sprayed Cr2 AlC coating in order to demonstrate the processing feasibility of Cr2 AlC MAX phases as a bond-coat layer.